(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This research presents an innovative astronomical model that transforms the lunar surface into a highly reflective mirror by heating it to the point where its soil melts, forming a glassy layer that enhances the reflection of sunlight. This increases nighttime illumination on Earth and reduces the sun’s heat by reflecting some of the radiation back into space. The study proposes a technical method for this by using nuclear missiles directed at specific areas of the lunar surface, transforming silica-rich sand into glass, similar to what happens in meteorite impacts. The research discusses the comparison between this idea and previous experiments, such as spraying calcium carbonate into the atmosphere to reduce the sun’s heat. The objective observation about the moon is the regular cycle of its phases (phases) and the constant change in the shape and size of the illuminated part of it excludes the possibility that the light emitted by the moon is of the moon itself, because it is impossible to imagine a natural process occurring on the surface of the moon that could light up and darken all its parts by way of a precise system that makes clear boundaries between darkness and light.